WOM Positive Towards Memorable Tourism Experiences and Risk Perception Mediated by Tourist Satisfaction - Sarrah Jessica Hidayat; Sugiarto Sugiarto; Tonny Hendratono (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This study examines the influence of memorable tourism experiences and operational risk management in tourist train transportation on positive Word of Mouth (WOM), with tourist satisfaction serving as a mediating variable. A quantitative approach was employed, and data were processed using SEM-PLS 4. The research sample consisted of 247 respondents who had used tourist train services within the past year. The results reveal that both effective risk management practices and memorable tourism experiences perceived by tourists significantly impact tourist satisfaction. Additionally, tourist satisfaction plays a crucial mediating role in generating positive WOM. The study highlights that memorable tourism experiences, including aspects such as comfort, scenic views, and the quality of service, significantly enhance tourist satisfaction. Furthermore, operational risk management, which includes ensuring passenger safety, maintaining service reliability, and handling emergencies effectively, is essential for cultivating satisfaction and positive WOM. The findings suggest that businesses in the tourism industry, particularly those operating tourist trains, should prioritize both risk management and creating memorable experiences to foster customer loyalty and enhance WOM. This study contributes to understanding the dynamic relationship between risk management, customer satisfaction, and WOM in the tourism sector, providing valuable insights for improving service strategies in tourist train transportation.